A rebar corrosion sensor embedded in concrete based on surface acoustic wave. (1st December 2020) - Xie, Liqiang; Zhu, Xifeng; Liu, Zhirong; Liu, Xiguang; Wang, Tianxian; Xing, Jianchun
Graphical abstract: Highlights: An embedded rebar corrosion sensing method is achieved based on SAW. The response signal of the SAW can evaluate the corrosion state of the rebar. The sensor is characterized by accelerated corrosion of the specimens. The sensitivity is 0.24 dB or 10.4°per 1% corrosion rate, the nonlinearity is 1.43%. Abstract: The detection of the corrosion of rebar using sensors is an effective method that is used to plan maintenance and to avoid accidents of civil structures. In this study, a novel embedded sensing method was developed based on surface acoustic wave (SAW). The sensor consisted of a SAW transducer and a pair of sensing electrodes. As the corrosion of the rebar changed the capacitance of the sensing electrodes, the reflection coefficient of the reflecting grating of the SAW transducer was also changed. Therefore, by analyzing the response signal of the SAW, the corrosion state of the rebar could be evaluated. To improve the sensitivity of the novel sensor, the structures of the SAW transducer and the sensing electrodes was designed with great care. The SAW transducer was fabricated using the lift-off process, and concrete specimens embedded with sensing electrodes were casted. The rebar corrosion sensor was characterized by accelerated corrosion of the specimens. The relative mass loss ratio was introduced as the corrosion degree in order to quantitatively evaluate the corrosion state of the rebar. The sensitivities of the sensor were 0.24 dB in amplitude per 1% corrosion degree and 10.4° in phase per 1% corrosion degree, and the nonlinearity in phase was 1.43%.